Implementation of Crowdsourcing Methods in Village Promotion Websites - Ahmad Akbar; Indri Sulistianingsih; Bagus Kurniawan (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study focused on the implementation of the Despro (Village Promotion) application, a web-based platform utilizing crowdsourcing methods to promote the potential of villages, tourist attractions, products, and services in Pari City. The primary objective was to create an effective tool for local governments and village communities to showcase their natural resources, cultural heritage, and local products. The Despro application enables user participation by allowing volunteers to contribute promotional content, thus fostering community engagement. Key features of the application include comprehensive village profile pages, user-uploaded content (such as photos, videos, and stories), a content rating system, search and filtering functionalities, digital map integration for location display, and a messaging system for user interaction. Additionally, the application incorporates a structured 'Tasks' feature, divided into three stages—Preparation, Process, and Completion—to facilitate organized promotional activities. The research employed the waterfall model for software development, encompassing stages of requirements analysis, design, implementation, testing, and evaluation. The results demonstrated that the Despro application effectively enhances the visibility of village potential in Pari City and significantly increases community involvement in rural tourism initiatives.